Severe asthma: characterisation, mechanisms & treatment - Chung, Fan (Henry Stewart Talks, 2012)
Definition and characterisation, From difficult-to-treat asthma to severe asthma, Phenotypes and characteristics, Current treatment modalities, Chronic airflow obstruction, Corticosteroid insensitivity, Future treatments: specific targets for specific phenotypes, Update interview: Biologic antibody therapies for severe asthma, Update interview: Type 2 high asthma characterised by interleukin 4, 5 and 13, Update interview: Biomarkers of Type 2 high asthma
Updated at 2022/05/25